2021
DOI: 10.1136/bmjopen-2020-044343
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of blood donation and associated factors in Ethiopia: a systematic review and meta-analysis

Abstract: ObjectiveTo assess the level of knowledge about blood donation and associated factors in Ethiopia.DesignSystematic review and meta-analysis.MethodsBoth published and unpublished cross-sectional studies on the level of knowledge about blood donation in Ethiopia were included. Articles from different databases such as PubMed/MEDLINE, HINARI, EMBASE, Scopus, Google Scholar and African Journals Online were searched. Cochrane I2 statistics were used to check for heterogeneity. Subgroup and sensitivity analyses of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
(19 reference statements)
2
8
0
Order By: Relevance
“…Evidence indicated that higher-level education increases the knowledge and positive attitude of individuals, thereby encouraging people to donate blood continually. 23 Attitude towards blood donation was found to be significantly associated with willingness to donate blood. Accordingly, the odds of willingness to donate blood in the future among study participants who had a favorable attitude was nearly 5 times higher as compared to those participants who had an unfavorable attitude.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Evidence indicated that higher-level education increases the knowledge and positive attitude of individuals, thereby encouraging people to donate blood continually. 23 Attitude towards blood donation was found to be significantly associated with willingness to donate blood. Accordingly, the odds of willingness to donate blood in the future among study participants who had a favorable attitude was nearly 5 times higher as compared to those participants who had an unfavorable attitude.…”
Section: Discussionmentioning
confidence: 93%
“…6 The shortage of blood is a common problem in health institutions globally, particularly in low and middle-income countries. 7 Approximately 80 million units of blood were collected from voluntary donors globally each year, though only 2 million units were collected in sub-Saharan Africa (SSA), where the need is very high. 8 In SSA, a total of 18 million units of safe blood are required annually, but only 15% were collected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 The other reason is that women are more likely to have physiological circumstances that prevent them from donating blood like menstruation and bleeding during pregnancy and delivery. 42 This suggests that women should be informed more about the health advantages of blood donation and health information delivery through campaigns and different sources of information.…”
Section: Discussionmentioning
confidence: 99%
“…7 However lower knowledge levels were noted in the study populace in Ethiopia and Jordan while higher levels of knowledge were found by investigators in Malaysia, India, and Benin City in Nigeria. [8][9][10][11][12] This could be due to differences in the assessment technique and demographic differences.…”
Section: Discussionmentioning
confidence: 99%